Alexandre Ribot - Schmidt, M.E. author. aut Link
196 p.
Keywords: In 1878 Alexandre Ribot assumed his place at the left-center of the French Chamber of Deputies. From here he began a lifelong effort to establish a moderate republic based upon his conception of liberal political values. The time seemed propitious to instill lofty purpose into French political life, for his entry into the Chamber coincided with the consolidation of the republican regime following the crisis of 16 May. But the first wave of republican anti-clericalism revealed the fragility of Ribot's hopes. During the next forty years, successive dramatic phases in republican history - Boulangism, the Dreyfus Affair, separa tion of church and state, the emergence of socialism, and ultimately, the demands of wartime leadership - would test Ribot's system of political values. Adaptive and resilient, he refined his definition of liberalism in response to political change and the charge that his plea for liberty and toleration had become instead sanctuary for a privileged class in French society.